Prototype of Hydroponic Lettuce Cultivation: IoT-Based Automatic Irrigation System for Growth Enhancement and Sustainability - Fina Amru Millati Millati; Anggraini Puspita Sari; Daniel Gloryo Nadirco; Norhaslinda Binti Hasim (IJCONSIST JOURNALS, 2024)
Lettuce (Lactuca sativa) is a vegetable commonly grown in temperate and tropical climates. In organic cultivation, lettuce has high economic value due to its high mineral content, including iodine, copper, iron, phosphorus, and others. Hydroponics is an agricultural cultivation method that uses water as the planting medium. This method offers advantages such as space efficiency and more. Currently, monitoring water in hydroponic plant cultivation is conducted periodically by growers who physically visit the cultivation site, including the reservoir tank. This process can be quite inconvenient because growers cannot predict when moisture levels will drop. One solution to this problem is to implement remote, real-time water monitoring for hydroponic lettuce cultivation using Internet of Things (IoT) devices. Therefore, a system design for IoT-based remote monitoring of moisture levels is required, allowing growers to monitor the condition of hydroponic lettuce without needing to visit the cultivation site. The research findings indicate that when the moisture level is dry, the system will display a value of 100, prompting users to receive a notification for irrigation. If the value is below 100, the system indicates that the planting medium is sufficiently moist.